2021
DOI: 10.1002/acp.3814
|View full text |Cite
|
Sign up to set email alerts
|

Spaced mathematics practice improves test scores and reduces overconfidence

Abstract: The practice assignments in a mathematics textbook or course can be arranged so that most of the problems relating to any particular concept are massed together in a single assignment, or these related problems can be distributed across many assignments-a format known as spaced practice. Here we report the results of two classroom experiments that assessed the effects of mathematics spacing on both test scores and students' predictions of their test scores. In each experiment, students in Year 7 (11-12 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 34 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Their participants also preferred (and were keener to engage in) a massed practice schedule for future training. Relatedly, other researchers have found that participants erroneously predict either no difference or better performance following a massed (versus spaced) practice schedule (e.g., Emeny et al, 2021;Logan et al, 2012;Simon & Bjork, 2001;Zechmeister & Shaughnessy, 1980). In terms of the testing effect, when asked to make item-based judgments of learning, individuals often indicate that they will remember restudied material better than tested material, when the opposite is nearly always true (e.g., Karpicke, 2009;Kornell & Son, 2009;Potts & Shanks, 2014;Roediger & Karpicke, 2006).…”
Section: Metacognition and The Learning Experiencementioning
confidence: 99%
“…Their participants also preferred (and were keener to engage in) a massed practice schedule for future training. Relatedly, other researchers have found that participants erroneously predict either no difference or better performance following a massed (versus spaced) practice schedule (e.g., Emeny et al, 2021;Logan et al, 2012;Simon & Bjork, 2001;Zechmeister & Shaughnessy, 1980). In terms of the testing effect, when asked to make item-based judgments of learning, individuals often indicate that they will remember restudied material better than tested material, when the opposite is nearly always true (e.g., Karpicke, 2009;Kornell & Son, 2009;Potts & Shanks, 2014;Roediger & Karpicke, 2006).…”
Section: Metacognition and The Learning Experiencementioning
confidence: 99%